Comprehensive Sexuality Education: A pending matter in Early Childhood Education in Mexico - Fernando Salinas-Quiroz; Adriana Rosales Mendoza (Pontificia Universidad Católica del Perú, 2016)
This paper stresses the need to incorporate Comprehensive Sexuality Education (CSE) during the Early Childhood and Preschool school stages in Mexico. A detailed analysis of the content of strategies, courses of action and policies for early education was made for both, the local and Latin-American level. Findings indicate that there remains a need for CSE for 0 to 6-year-old Mexican children. The inclusion of a human rights and a sociocultural perspective of gendered sexuality is strongly recommended. Early life-course interactions between children and their caregivers have the potential to influence developmental outcomes in an enduring manner because they become internalized in the form of generalized mental representations. CSE encompasses the history of care where consistent and coherent secure base support is needed.